Effects of Hybrid Nanocooling-Lubricants MQCL on Machining Temperature and Tool Wear Mechanisms under Turning Process of Titanium Alloy - Lim, Syh Kai; Ahmad Razlan, Yusoff (J-Global, 2023)
Minimum quantity lubrication (MQL) has performed optimum lubrication but poor cooling during turning process. Thus, hybrid nanocooling-lubricants for minimum quantity cooling-lubrication to achieve sufficient lubrication and cooling effect for high speed turning titanium alloy (Ti6Al4V) material. This study is targeted on the machinability performance of G-Al2O3 hybrid nanocooling-lubricants MQCL and conventional fluids cooling condition with variable cutting speeds at constant feed rate as input parameters to evaluate the machining temperature and cutting insert flank wear as quality responses. Scanning electron microscopy-energy dispersive X-ray (SEM-EDX) analysis was implemented to determine Ti6Al4V workpiece chemical elemental deposition on the cutting insert flank surface. Experimental results obtained that significantly increased of machining temperature from 206°C to 317°C based on type-K thermocouple wire measurement as the increment of cutting speeds from 120 m/min to 180 m/min. However, machining temperature decreased with the increasing of lubrication flow rate of MQCL 10 mL/min to 40 mL/min, then to the conventional fluids cooling condition. The comparison to conventional fluids cooling condition, the G-Al2O3 hybrid nanocooling-lubricants MQCL at the cutting speed of 120 m/min significantly increased tool life for 51% and cutting speed of 180 m/min for 28%, respectively. Furthermore, SEM-EDX has presented that titanium element deposited on cutting insert flank surface, which has shown micro-attrition, abrasion and adhesion wear leading edge chipping or fracture are identified as the main tool wear mechanisms